Modelling of ultrasonic impact treatment (UIT) of welded joints and its effect on fatigue strength (Fracture and Structural Integrity, 2015)
Ultrasonic impact treatment (UIT) is a remarkable post-weld technique applying mechanical impacts in combination with ultrasound into the welded joints. In the present work, a 3D simulation method including welding simulation, numerical modelling of UIT-process and an evaluation of fatigue crack growth has been developed. In the FE model, the actual treatment conditions and local mechanical characteristics due to acoustic softening are set as input parameters. The plastic deformation and compressive stress layer are found to be more pronounced when acoustic softening takes place. The predicted internal residual stress distributions of welded joint before and after UIT are compared with experimental results, showing a fairly good agreement with each other. Finally, simulated results of fatigue crack growth in various residual stress fields are well compared with test results, so that the proposed model may provide an effective tool to simulate UIT-process in engineering structures.
Keywords: Residual stress